Opportunities for human resources for health and rehabilitation: a response to Jesus et al - Power, Jessica; McVeigh, Joanne; Gilmore, Brynne; MacLachlan, Malcolm (Human resources for health, 2017)
We welcome Jesus et al.'s paper, which makes an important contribution to the under-researched area of the physical rehabilitation workforce. The authors present recommendations to "advance a policy and research agenda for ensuring that an adequate rehabilitation workforce can meet the current and future rehabilitation health needs" (p. 1). We argue that their perspective could however be strengthened by adopting a stronger global perspective, including consideration of the needs of low-resource settings. In particular, we highlight the integral role of more effective sector and inter-sectoral governance, the opportunity to support the development of community-based rehabilitation (CBR), the lessons that can be learnt from human resources for health (HRH) research and practice more generally, and the recent developments in the global provision of assistive technologies. Each of these issues has important implications and contributions to make to advance the policy and research agenda for the global rehabilitation workforce.
Keywords: Workforce; postup; “Global Health”; zdravotnické zdroje; Health Resources; Humans; Policy; Rehabilitation; lidé